PEG-PLGA core–shell nanoparticles for the controlled delivery of picoplatin–hydroxypropyl β-cyclodextrin inclusion complex in triple-negative breast cancer: In vitro and in vivo study - Nafie Mohamed S.; Sedky Nada K.; Hassan Hatem A. F. M.; Fawzy Iten M.; Abdelhady Manal M. M.; Bakowsky Udo; Fahmy Sherif Ashraf (Nanotechnology Reviews)
In this study, we prepared an inclusion complex of picoplatin (Pc) with 2-hydroxy propyl β cyclodextrin (HPCD) to improve its hydrophilicity, yielding Pc-HPCD. The Pc-HPCD complex was encapsulated into PEG-PLGA nanoparticles (NPs) using the emulsion–solvent evaporation method, yielding Pc-HPCD@PEG-PLGA core–shell NPs. The inclusion complex was assessed using 1HNMR spectroscopy and a phase solubility study. In addition, the average hydrodynamic diameter, polydispersity index, zeta potential, and encapsulation efficiency (EE%) of the Pc-HPCD@PEG-PLGA NPs were 190.2 ± 8.7 nm, 0.14 ± 0.02, −13.97 ± 0.67 mV, and 80.7 ± 2.4%, respectively. In vitro release study showed a pH-triggered release manner. Furthermore, the biological evaluation of Pc-HPCD@PEG-PLGA NPs revealed a significantly potent cytotoxic activity (IC50 = 1.6 ± 0.24 µg/ml) against triple-negative breast cancer cells (TNBC), surpassing that of Pc-HPCD (IC50 = 5.3 ± 0.93 µg/ml) and Pc (IC50 = 7.5 ± 0.4 µg/ml). Pc-HPCD@PEG-PLGA NPs induced significant apoptosis and the ability to arrest cells at the sub-G1 phase in MDA-MB-231 cells. Moreover, in an in vivo model established using SEC-bearing mice, treatment with Pc-HPCD@PEG-PLGA demonstrated significant inhibition of tumor proliferation (67.2%). This was accompanied by improvements in hematological and biochemical measurements, as well as histopathological examination, which indicated a reduction in cellular and nuclear pleomorphism. Our study demonstrated the potential of Pc-HPCD@PEG-PLGA NPs to be employed as an effective and safe therapy capable of conquering TNBC.